Propriedades óticas dos aerossóis no Pantanal Mato-grossense - Brunelli, Thais Costa (2020)
Aerosols are solid or liquid particles, which are suspended in the Earth's atmosphere. Atmospheric research seeks to characterize the optical properties of these aerosols as well as to understand their interaction process with solar radiation. This research focuses on the optical properties of aerosols in the Pantanal Mato-grossense, presenting an estimate of these and the seasonal behavior in the years 2017, 2018 and 2019. The parameters investigated were the absorption coefficient - b(525 nm)abs, as well as the scattering coeficiente - b(525 nm)scat, extinction coeficiente - b(525 nm)ext, optical extinction depth - AOD (525 nm), single scattering albedo - SSA525 nm, and angstrom absorption coefficient - α(370 ,590). Data collected from a Nephelometer were explored, with spectral measurements of the scattering coeficiente (b(λ)scat), as well as data from an Aetalometer that provides directly the mass concentration of black carbon [BC(λ) ]. Here we show that during the investigated triennium, the optical properties of aerosols have particular spectral characteristics in the rainy and dry periods of each year. We sought to evaluate the influence of exogenous factors to aerosol measurements, events resulting from biomass burning is the main factor for the change in optical properties. It was found that the AOD (525 nm), has a seasonality very well outlined to the monthly behavior of the record biomass burning. It was found that the AOD (525 nm) has a seasonality very well outlined to the monthly biomass burning behavior. During the dry period, with the increase in biomass burning, it was possible to observe an average reduction of up to 45% in the photosynthetically active radiation (PAR) incident on the surface of the ecosystem, while in the rainy period this reduction is less than 23%. It is evaluated through SSA that during the rainy period aerosols favor the scattering of solar radiation, whereas in the dry period there is an intensification of absorptive processes. The biomass burning events in the state of Mato Grosso influence the population dynamics of aerosols present in the Pantanal atmosphere as well as the quality and quantity of radiation that is available for the maintenance of this ecosystem.